2009
DOI: 10.1108/09513570910987358
|View full text |Cite
|
Sign up to set email alerts
|

Religious “spirit” and peoples' perceptions of accountability in Hindu and Buddhist religious organizations

Abstract: PurposeThe purpose of this paper is to examine how the Buddhist and Hindu people in non‐Western societies perceive rational accountability practices in religious organizations, through their respective religious “spirit” and “beliefs” and in combination with broader structural elements of the society.Design/methodology/approachThe interpretive tradition of research, i.e. ethnography based on two in‐depth cases from Sri Lanka (a Buddhist temple) and Mauritius (a Hindu temple) is adopted for the data collection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
2
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 54 publications
1
44
2
8
Order By: Relevance
“…Accordingly, they thought there was no need to prepare a budget. This is consistent with the results of the study conducted by Jayasinghe and Soobaroyen (2009). In that study they found that there was very little formal planning and budgeting involved within the Hindu temples and the treasurer informally prepares the budget more as a way to plan for significant cash payments rather than for approval or authorization.…”
Section: Budgetary Controlssupporting
confidence: 81%
See 3 more Smart Citations
“…Accordingly, they thought there was no need to prepare a budget. This is consistent with the results of the study conducted by Jayasinghe and Soobaroyen (2009). In that study they found that there was very little formal planning and budgeting involved within the Hindu temples and the treasurer informally prepares the budget more as a way to plan for significant cash payments rather than for approval or authorization.…”
Section: Budgetary Controlssupporting
confidence: 81%
“…Many nonprofit organizations, particularly in the case of religious organizations, assume a high level of morality among their members and staff (Bowrin 2004;Jayasinghe and Soobaroyen 2009). Given this, 'secular' controls, such as accounting, appear not to be important.…”
Section: The Issue Of Trustmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover the religious values, an example of Laughlin's "cultural beliefs and values, (Laughlin, 1991, page 213) are shared by both the accrediting team and the hospital staff. Accordingly, hospital staff suggest that these shared religious beliefs provide the motivation for complying with all the demands of the accreditation programme (Jayasinghe & Soobaroyen, 2009;Lewis, 2001). …”
Section: Accreditation Of Religious Standards and Shared Religious Vamentioning
confidence: 99%